Aktivitas Gastroprotektif Kombinasi Madu Dan Virgin Coconut Oil (Cocos nucifera) Pada Model Tikus Tukak Lambung - Widyastuti, Lita; Herowati, Rina; Ariawan, M Wahyu; Purwidyaningrum, Ika (Faculty of Pharmacy, Universitas Muslim Indonesia, 2024)
Gastric ulcers are damage that occurs to the mucosal tissue, submucosa and the muscle layer of the stomach, this condition is caused by hypersecretion of stomach acid. The substance content of VCO has a gastroprotective effect because it includes flavonoid compounds, phenols, catalase, ascorbic acid, and vitamin E, while VCO includes octanoic acid, δ-Octalactone, dodecanoic acid, δ-Decalactone, acetic acid. The aim of this research is to understand the gastroprotective activity resulting from giving a combination of honey and VCO to aspirin-induced rats. Honey and VCO in single administration include one dose, namely 14 ml/kgBW honey and 10 ml/kgBW VCO, while in combination treatment three doses are given, namely 10.5; 7; 3.5 ml/kgBB honey and 7.5; 5; 2.5 ml/kgBB VCO. Then in the combined treatment, 5 variations of doses were given, namely honey and VCO (7:7.5); (7:5); (7:2.5); (10.5:5); (3.5:5) ml/kgBB. TNFα levels before being induced by aspirin, after being induced by aspirin, after honey and VCO therapy, and macroscopic observations on a single treatment showed that administration of honey and VCO at doses of 10.5 ml/kgBW and 5 ml/kgBW showed a gastroprotective effect compared to other doses. Then, in histopathological testing, doses with gastroprotective effects can restore mucosal cell cohesion which has been previously damaged due to erosion. The combination of honey and VCO showed gastroprotective results at a dose of 10.5 ml/kgBB honey and 5 ml/kgBB VCO.